Association Between Body Mass Index and Female Sexual Dysfunction: A Cross-sectional Study from the Data Registry on Experiences of Aging, Menopause, and Sexuality. Issue 10 (5th August 2020) - Faubion, Stephanie S.; Fairbanks, Flavia; Kuhle, Carol L.; Sood, Richa; Kling, Juliana M.; Vencill, Jennifer A.; Mara, Kristin C.; Kapoor, Ekta
Abstract: Background: Obesity and female sexual dysfunction (FSD) are prevalent conditions, and both are associated with significant adverse effects on health and well-being. Aim: To investigate the association between body mass index and FSD, as well as potential moderators. Methods: This cross-sectional study was performed by analyzing medical records of 6, 688 women seeking consultation for menopause-related or sexual health–related concerns at women's health clinics at Mayo Clinic Rochester, MN, and Scottsdale, AZ, between May 1, 2015, and September 15, 2019. Outcomes: Female sexual function was assessed by the Female Sexual Function Index, and sexual distress was assessed by the Female Sexual Distress Scale-Revised. Results: Being overweight or obese was associated with a lack of sexual activity. Among sexually active women, those who were overweight or obese had lower Female Sexual Function Index total scores and sexual function domain scores (indicating worse sexual function), including sexual arousal, lubrication, satisfaction, orgasm, and pain, and higher levels of sexual distress than those with normal weight. However, on multivariable analysis, these associations were found to be mediated by other factors, including age, level of education, reproductive stage, medication use, and mood disturbances, which are known to impact body weight and sexual function in women. Clinical Implications: Overweight and obesity were associated with sexual inactivity and greater odds of having FSD, which should prompt proactive assessment of sexual function. Strengths and Limitations: The strengths of this study include the large cohort size and assessment of sexual problems in addition to sexual distress, a key component of the definition of sexual dysfunction. This study also took into account multiple potential moderating factors. Limitations include the cross-sectional design, which precludes determination of causality as well as lack of diversity in the cohort, potentially limiting generalizability of results. In addition, sexual function was not assessed in women reporting no recent sexual activity, which may confound results. Conclusion: Overweight/obesity and FSD are highly prevalent conditions, which appear to be indirectly associated. These results highlight the need to identify and address FSD in all overweight and obese women, with particular attention to potential contributing factors.